Caracterização e avaliação in-vitro de biovidro experimental em microparticulas para o tratamento da hipersensibilidade dentinária cervical - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2016)
Bioglass has been shown as a bioactive material, in contact with human body. It can be used in several clinical dental conditions, such as cervical dentine hypersensitivity (CDHS). The objectives of this present study were to characterize the physical, chemical, biological behavior and dentin permeability reduction. The bioglass powder formulation: 2Na2O.1CaO.3SiO2- 6% P2O5 (BV1) and their different compositions, 2Na2O.1CaO.3SiO2- 6% P2O5- K2CO3 (BV2); 2Na2O.1CaO.3SiO2- 6% P2O5-SrO (Bv3) were synthesized by the melt method. Commercial bioglass 45S5® (BV4) and Biosilicate® (BV5) were used as controls positive. All bioactive glasses were characterized by scanning electron microscopy by field effect, infrared spectroscopy with Fourier transform, X-ray diffraction and spectroscopy micro-Raman to confirm the crystallinity and microstructure and chemical composition. Biocompatibility test: cell culture (3T3 fibroblasts); the bioactive glasses were placed in culture medium in three concentrations (100, 10 and 1 mg/mL) and the supernatant was used to evaluate cell proliferation. The antimicrobial effect was evaluated with Staphylococcus aureus (ATCC® 25923), Escherichia coli (ATCC® 25922), Pseudomonas aeruginosa (ATCC 27853) were tested by microdilution, minimum inhibitory concentration (CIB) and minimum bactericidal concentration (MBC). The dentin permeability reduction was evaluated on bovine dentine in 3 stages: minimum permeability, maximum permeability (after EDTA 24%) and permeability final (after biomaterial). The samples were stored in 24-well plates (37.5oC) in artificial saliva with and no simulated brushing. The results showed all biomaterials had similar bioglass characteristics. In cell culture there was an increase in proliferation (significant difference between the Bv1-10 groups and 1 mg / ml, BV4 - 10 mg / ml and BV5 - 1 mg / ml. The bioglass Bv3 presented antimicrobial effect not statistically significant compare to the positive control (0.12% chlorhexidine). All biomaterials were promoted dentin permeability reduction, however there was a significant difference considering the group factors (bioactive glasses) and treatment (with and without brushing simulated). Considering the results it can be conclude that bioactive glasses were not cytotoxic; not show a broad spectrum antimicrobial however should be carried out other methodologies, all experimental bioglasses show dentin permeability reduction. !
Characterization and In-vitro evaluation of an experimental Microparticulate Bioglass for treatment of cervical dentinal
Keywords: Vidro; Teste de biocompatibilidade; Sensibilidade da Dentina; Permeabilidade da dentina; Glass; Biocompatibility test; Dentin sensitivity; Dentin permeability; Ciência da Saúde - Odontologia